Drosophila Melanogaster - Model for Recent Advances in Genetics and Therapeutics 2018
DOI: 10.5772/intechopen.73077
|View full text |Cite
|
Sign up to set email alerts
|

Swiss Cheese, Drosophila Ortholog of Hereditary Spastic Paraplegia Gene NTE, Maintains Neuromuscular Junction Development and Microtubule Network

Abstract: Neuropathy target esterase (NTE) is a molecular target for the organophosphorus compound-induced delayed neuropathy (OPIDN) and also one of the genetic factors responsible for the development of the hereditary spastic paraplegia (HSP), characterized by axon degeneration of motoneurons causing progressive lower-limb spastic paralysis. Both HSP and OPIDN are characterized by the distal axonopathy. The molecular mechanisms underlying the axonopathy involved in HSP and OPIDN are poorly understood. In order to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…A plethora of experiments shows that the ablation of HSP-related genes infers mitochondrial dynamics in axons, however, sometimes indirectly, through an endoplasmic reticulum state [ 106 , 107 , 108 , 109 , 110 ]. Furthermore, we have previously found SWS to be present presynaptically in larval neuromuscular junctions, and its dysfunction altered their organization, influencing mitochondria distribution [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of experiments shows that the ablation of HSP-related genes infers mitochondrial dynamics in axons, however, sometimes indirectly, through an endoplasmic reticulum state [ 106 , 107 , 108 , 109 , 110 ]. Furthermore, we have previously found SWS to be present presynaptically in larval neuromuscular junctions, and its dysfunction altered their organization, influencing mitochondria distribution [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mutations in sws develop axonal and glial pathology and neuronal apoptosis. Additionally, the SWS protein was recently shown to play a role in the maintenance of neuromuscular function development and microtubule networks [88]. The sws gene is the ortholog of the neuropathy target esterase (NTE) gene, which is one of the genetic factors responsible for the development of hereditary spastic paraplegia [88].…”
Section: Electrical Insulation Of Axonsmentioning
confidence: 99%
“…Additionally, the SWS protein was recently shown to play a role in the maintenance of neuromuscular function development and microtubule networks [88]. The sws gene is the ortholog of the neuropathy target esterase (NTE) gene, which is one of the genetic factors responsible for the development of hereditary spastic paraplegia [88]. In both vertebrates and invertebrates, the insulating of axons by glial processes is the only way to increase the conduction velocity of electrical impulses.…”
Section: Electrical Insulation Of Axonsmentioning
confidence: 99%
“…It was also initially shown that glial hyperwrapping exists in sws mutants [ 9 ]. In our previous work, we found that sws was mainly detected on the surface of the ventral nerve cord, in abdominal nerves, and presynaptically at the neuro-muscular junctions of PNS of the 3rd instar larvae [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This leads to locomotor deficits due to both neuronal and glial dysfunction. For instance, neuromuscular junction alterations are accompanied with by an active zone decline and postsynaptic reaction to this deterioration due to the neuronal sws KD in Drosophila [ 40 ]. The human sws orthologue is associated with several syndromes of the spasticity—ataxia continuum caused by neurodegeneration in the spinal cord, cerebellum, and/or pituitary gland [ 67 ].…”
Section: Discussionmentioning
confidence: 99%